The Future We Live In - Tikhomirova, Anna (Journal of Economic Sociology, 2024)
The book “The Future of Consumption” offers the readers to take a look at the trends in the modem retail industry and their impact on the future of consumption. The editors, Kristina Backstrom, Carys Egan-Wyer, and Emma Samsioe, present the material in a deductive manner by first outlining the general topic of each part that provides the reader with the general idea. They guide the reader through technological, sustainable, wellbeing, and customer experience factors, all of which are closely interlinked and shape consumption practices. They further divide parts into smaller elements, with each reflecting on the crucial tendencies within the modern consumption practices, which are to determine the future of consumption. In each chapter, the authors unpack the integral elements of modern consumption discourse that by the end of the book helps the reader assemble the jigsaw puzzle and get a complete understanding of the future of consumption. Even though the book presents a purely marketing standpoint and manifests itself as a guide for market researchers and practitioners, the reader can find a lot of evidence that the factors described have a much deeper societal nature beyond just consumption patterns. Modern consumption is no longer only about obtaining and utilizing goods and services. It is about self-identity and self-definition, when through consumption people tell who they are, what social stand they represent, and what values and beliefs they reflect. The role of the retailer is also undergoing certain transformations. Modern retailers and brands are seen as the transmitters of social and political ideas, those who are able to shape public opinion and significantly alter consumption behavior. All the players of modern retail are interconnected and affect one another.